Firm Size and Dividend Payouts - Redding, Lee S. (Journal of Financial Intermediation, 1997)
This paper presents a model of large institutional and small individual investors choosing stocks. Dividend policy of firms is determined by the preferences of the resulting stockholders. Large investors choose to invest in large corporations because it lowers their transaction costs. Since these institutions prefer dividends, the large corporations choose to pay dividends, while the small corporations, owned by individuals, do not. The results show that firm size and liquidity explain the decision ofwhetherto pay dividends well, whereas existing informational explanations (such as monitoring and signaling) explain thelevelof dividends well.Journal of Economic LiteratureClassification Numbers: G32, G35, G11.